Impact of Building Orientation on Market Value: Koya municipality as a case study - VIAN A. SHAREEF; SORAN K. OMER; HALGURD S. MAGHDID (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The study aims to investigate the impact of building orientation on market value, it's an exploratory study about inhabitants, house customers and owners of real estate offices opinions in the municipality of Koya, as well the building orientations which include eight orientations as independent variable such as north, northeast, east, southeast, south, southwest, west and northwest, also market value as a dependent variable of the study. A questionnaire involving 9 items has been set and distributed through online link as the research sample, the size of the population of the study is 126 residents which were randomly they collected. Then, all of them have been analyzed as the appropriate statistical method is used to analyze data to test research hypotheses via using the regression of SPSS program. Finally, the research has several conclusions mainly is the building orientation has the small impact on the market values, also the research recommended that we should not ignore the orientation that preferred by Koya’s inhabitants which should focus on the factors that effect on house supplies and demands in the city.